Excluding Emotions: The Performative Function of Populism - Emmy Eklundh (Coordinamento SIBA, 2020)
Populists are often excluded from political life on the basis that they are too emotional. Both social movements as well as political parties who are labelled as populist are accused of using demagoguery and manipulation in order to attract support and new membership. Often, these critiques emanate from the political establishment, creating a division between emotional and rational actors in politics. In this article, I argue that instead of seeing populism as a nominal or ordinal category, we should look at how the term itself has performative properties. The article is interested in how populism as a concept is used as a tool for exclusion, and how being ‘too emotional’ is used as justification for excluding certain actors. This article first contends that this perspective is endemic to political and social theory, and has long been utilised to marginalise women, non-Europeans, or young people. Second, the article demonstrates how this perspective also pervades much of contemporary studies on populism, which do not sufficiently recognise the political implications of employing a strict divide between emotion and reason. Third, the article further contends that by using a Laclauian framework which sees politics as equal to hegemony as equal to populism, one can conclude that populist actors are no different from other political actors; emotions and affects are always central to any political identity. Instead, the division between emotional and rational in politics serves to sediments exclusionary practices against newcomers and challengers of the status quo. I conclude by using the Laclauian framework, focus can be turned to the performative function of populism, and its political implications.